2011
DOI: 10.1007/s12072-011-9303-x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus (genotype 4)-associated mixed cryoglobulinemia vasculitis: effects of antiviral treatment

Abstract: The results indicated that treatment with PEG-IFN alfa-2a plus ribavirin can achieve a complete clinical response in patients with HCV-related MC. Complete clinical response correlates with the eradication of HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…When comparing RCTs versus non-RCT studies, we observed a pooled SVR rate of 60% (CI: 53–68%) in the six RCTs[10, 13, 16, 18, 54, 93] compared to 52% (CI: 49–55%) in 45 non-RCTs[11, 12, 14, 15, 27, 28, 34, 35, 3742, 45, 46, 48, 53, 55, 56, 59, 62, 63, 6567, 69, 7173, 7581, 8385, 88, 90, 91, 95, 96] (Figure 3). This finding was statistically significant with p =0.043.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…When comparing RCTs versus non-RCT studies, we observed a pooled SVR rate of 60% (CI: 53–68%) in the six RCTs[10, 13, 16, 18, 54, 93] compared to 52% (CI: 49–55%) in 45 non-RCTs[11, 12, 14, 15, 27, 28, 34, 35, 3742, 45, 46, 48, 53, 55, 56, 59, 62, 63, 6567, 69, 7173, 7581, 8385, 88, 90, 91, 95, 96] (Figure 3). This finding was statistically significant with p =0.043.…”
Section: Resultsmentioning
confidence: 96%
“…There were 51 studies with a total of 11,102 HCV-4 patients included in the primary analysis (Table 1)[1016, 18, 27, 28, 34, 35, 3742, 45, 46, 48, 53–56, 59, 62, 63, 6567, 69, 7173, 7581, 8385, 88, 90, 91, 93, 95, 96]. The majority of studies (40/51, 78%) originated from the Middle East[1013, 15, 16, 18, 27, 28, 34, 35, 37, 4042, 45, 46, 53–56, 59, 62, 63, 66, 67, 69, 72, 75, 78, 80, 81, 8385, 88, 91, 95] and Europe (9/51, 18%)[14, 38, 39, 65, 71, 76, 79, 93, 96].…”
Section: Resultsmentioning
confidence: 99%
“…Available data about the role of SVR in MC CHC treatment were quite heterogeneous because treatment with standard IFN and PEG-IFN with different genotypes and populations were included. Global SVR ranges from 30 to 52 % [10,11], and these lower rates of virological response are likely related to some characteristics of these populations when compared to MC-negative patients. For example, in the examined studies [37], only symptomatic MC patients were included, and consequently, a considerable number of co-morbidities were present with a probable impact on virological response and rate of treatment interruption.…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab monotherapy effectively alleviated MC symptoms in about 71.4%84% HCV patients [111,112] . Rituximab given in combination peg IFNaribavirin was evaluated in patients with severe HCVcryo, resistant to IFNa combination therapy.…”
Section: Antiviral Treatmentmentioning
confidence: 98%